PENGARUH KOMPETENSI PROFESIONAL, KOMPETENSI PEDAGOGIK DAN MOTIVASI GURU TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI SE-KECAMATAN SEKUPANG BATAM DI MASA PANDEMIK COVID-19 - Putri, Stevanie Anggi (Jurnal Dedikasi Pendidikan, 2022)
This study aims to analyze the effect of professional competence, pedagogic competence and teacher motivation on the performance of public elementary school teachers in the Sekupang Batam district during the COVID-19 pandemic. The research method uses a quantitative approach, with a sample of 395 respondents. Data collection techniques through questionnaires, interviews, and document analysis to analyze teacher performance. The results showed that the variables of professional competence, pedagogic competence and teacher motivation simultaneously and significantly affected the performance of education personnel. The results of the t-test indicate that the variables of professional competence, pedagogic competence, and teacher motivation have a significant influence on teacher performance. The coefficient of determination of 0.576 indicates that 57.6% of teacher performance is simultaneously influenced by the variables of professional competence, pedagogic competence, and teacher motivation